Job retention during the Covid-19 pandemic - Pernille Valentin Borgensgaard (Danmarks Nationalbank, 2022)
Following the outbreak of the covid-19 pandemic, countries worldwide adopted new or scaled up existing job retention schemes. This paper examines the labor market effects of the Danish wage compensation scheme for employees, which offered wage subsidies to private firms that furloughed workers instead of laying them off. Using payroll records at the monthly frequency for Danish employer-employee matches, I find that the scheme prevented at least 10,400 exits from employment. However, it also compensated workers that firms were not planning to lay off. It mainly prevented job losses for low-tenured workers (È 1 year), while high-tenured workers (8+ years) would, to a lesser extent, have been laid off even in the absence of the scheme. Further, the scheme led to a significant decline in furloughed workers' labor income, which may reflect that firms negotiated wage cuts with their employees before applying for wage compensation. Finally, I find that labor market mobility was basically unaffected by the scheme.
Keywords: H12; J24; J38; J63; 330; Coronavirus; Lohnsubvention; Beschäftigungseffekt; Dänemark